Miskonsepsi Asam Basa Berbasis Multipel Representasi pada Lintas Jenjang Pendidikan - Isnaini Yunitasari; Hayuni Retno Widarti; Nazriati Nazriati (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study aims to describe acid-base misconceptions across levels of education using multiple representation based diagnostic tests. The research method is quantitative descriptive. Analysis process of misconceptions using modified CRI. The validity of diagnostic tests is between 0.197 to 0.798, and reliability is 0.753 and 0.626. The research subjects were 224 people consisting of class XI students, class XII students, second semester students, and 4th semester students. The results showed that the average percentage of acid-base misconceptions in class XI students to 4th semester students respectively was 50.30%; 56.84%; 53.81%; and 41.07%. Misconceptions that often occur in students and students related submicroscopic representations. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan miskonsepsi asam basa pada lintas jenjang pendidikan menggunakan tes diagnostik berbasis multipel representasi. Metode penelitian adalah deskriptif kuantitatif. Cara analisis miskonsepsi menggunakan CRI termodifikasi. Validitas tes diagnostik antara 0,197 hingga 0,798, dan reliabilitas sebesar 0,753 dan 0,626. Subjek penelitian sebanyak 224 orang yang terdiri dari siswa kelas XI, siswa kelas XII, mahasiswa semester II, dan IV. Hasil penelitian menunjukkan rata-rata persentase miskonsepsi asam basa pada siswa kelas XI hingga mahasiswa semester IV secara berurutan adalah 50,30%; 56,84%; 53,81%; 41,07%. Miskonsepsi yang sering terjadi pada siswa dan mahasiswa terkait representasi submikroskopik.